2017
DOI: 10.21275/art20174976
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and Immunological Study of Rheumatoid Arthritis

Abstract: The bacterial isolation evaluate for morphological testes and biochemical microscopy, as well as identification by Api system. The highest frequency of inflectional bacteria was E. coli (41.97%), followed by E. cloacae (21.25%), P. aeruginosa (12.5%), Salmonella (10%), K. pneumoniae (7.5%) and S. marcescens (6.25%). The concentration of some cytokines IL-6, TNF was measuredby using ELISA technical. The results showed significant decrease at P≤0.05 in level of IL-6for patient serum (23.76 ± 14.01 pg/ml)compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results of this study indicated that the highest rate of infection with E.coli was found in the age group(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) months by (48%), followed by the age group of (12-24) months by (28%), and the age group (36-48) by (14%). While the lowest rate of infection with E.coli was within the age group (24-36) months by(6%), and the age group (48-60) months by (4%), as shown in Table(2).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The results of this study indicated that the highest rate of infection with E.coli was found in the age group(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) months by (48%), followed by the age group of (12-24) months by (28%), and the age group (36-48) by (14%). While the lowest rate of infection with E.coli was within the age group (24-36) months by(6%), and the age group (48-60) months by (4%), as shown in Table(2).…”
mentioning
confidence: 71%
“…The results of the sero-typing method, showed that the Entero pathogeing groups of E.coli are represented by (7) The results of the current study revealed that the phylogenetic group E was the predominant (52%, 26/50) for isolates that possess the genes arpA, TrpBA, ChuA, ArBAgpE andTspE4c2.STEC has been classified into two main groups, O157 which causes hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUC), and nonlife-threatening O157, which are represented by a group of serotypes in the current study which are (O111:K58, O55:K59,O119:K69,O25:K11,O142:K86) according to the serotyping method as shown in Table (5) which shows the distribution of serotypes of the phylogenetic group of E. coli from diarrheal cases of children less than five years old. E. colistrains causes of food-borne diseases, food-producing animals such as cows and chickens which are the main reservoirs of many foodborne pathogens that produce Shiga toxin, which cause millions of cases of sporadic diseases and chronic complications.…”
Section: Resultsmentioning
confidence: 99%